Palaeomagnetic study of a subaerial volcanic ridge (Sao Jorge Island, Azores) for the past 1.3 Myr: evidence for the CobbMountain Subchron, volcano flank instability and tectonomagmatic implications - Silva, P. F.; Henry, B.; Marques, F. O.; Hildenbrand, A.; Madureira, P.; Mériaux, C. A.; Kratinová, Z. (Zuzana) (Geophysical Journal International, 2012)
We present a palaeomagnetic study on 38 lava flows and 20 dykes encompassing the past 1.3 Myr on S. Jorge Island (Azores Archipelago—North Atlantic Ocean). The sections sampled in the southeastern and central/western parts of the island record reversed and normal polarities, respectively. They indicate a mean palaeomagnetic pole with a latitude shallower than that expected from Geocentric Axial Dipole assumption, suggesting an effect of non-dipolar components of the Earth magnetic field. Virtual Geomagnetic Poles of eight flows and two dykes closely follow the contemporaneous records of the Cobb Mountain Subchron (ODP/DSDP programs) and constrain the age transition from reversed to normal polarity. Volcano flank instabilities, probably related to dyke emplacement along an NNW–SSE direction, led to southwestward tilting of the lava pile towards the sea.